2005
DOI: 10.1097/01.gim.0000187162.28070.a7
|View full text |Cite
|
Sign up to set email alerts
|

Tay Sachs disease carrier screening in schools: Educational alternatives and cheekbrush sampling

Abstract: computer-based resource versus an oral educational presentation and (2) blood sampling for enzyme and genetic testing versus cheekbrush testing for genetic sampling alone. Results: The education session was effective in significantly increasing students' knowledge (10.5% Ϯ 1.2%, P Ͻ .0001) and decreasing their anxiety about being a carrier (Ϫ12.2% Ϯ 1.6%, P Ͻ .0001). For the students, no significant differences were found between the computer-based resource and oral presentation. There were significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 31 publications
1
50
4
Order By: Relevance
“…Furthermore, although there was a large variation, the survey participants generally had a low mean level of knowledge about inheritance, which has earlier been reported as a reason for declining. 15 -17 Fear for needles seemed to be the most important reason for declining to participate in a Tay -Sachs screening programme among school-aged Ashkenazi Jews, 19 but it was of no importance in our study. Although 8% of the offer acceptors stated that they perceived limited benefits from participation, and 23% of them reported that they would draw no reproductive consequences from the test results (see Table 3), a finding also reported by Poppelaars et al, 21 their intention to participate might be due to social pressure, as they perceived more social influence from their partners in this study.…”
Section: Determinants Of Intention and Participationcontrasting
confidence: 43%
See 1 more Smart Citation
“…Furthermore, although there was a large variation, the survey participants generally had a low mean level of knowledge about inheritance, which has earlier been reported as a reason for declining. 15 -17 Fear for needles seemed to be the most important reason for declining to participate in a Tay -Sachs screening programme among school-aged Ashkenazi Jews, 19 but it was of no importance in our study. Although 8% of the offer acceptors stated that they perceived limited benefits from participation, and 23% of them reported that they would draw no reproductive consequences from the test results (see Table 3), a finding also reported by Poppelaars et al, 21 their intention to participate might be due to social pressure, as they perceived more social influence from their partners in this study.…”
Section: Determinants Of Intention and Participationcontrasting
confidence: 43%
“…Factors affecting the decision to accept or decline carrier screening for CF have recently been reviewed by Chen et al 15 Important acceptance factors included 'higher perceived benefits' (eg, not having an affected child, knowing one's carrier status), 'weaker perceptions of barriers' (eg, social stigma, psychological harm), and 'having fewer or no children'. Acceptance factors reported elsewhere were lower perceived negative consequences of test results, 17 more knowledge, 16,17,19 strong perception of the severity of the disease, 15,20,21 high perceived susceptibility, 15,22,23 and higher socioeconomic status, female gender, and age. 15 Important factors for declining, reported by Chen et al, 15 included perceived barriers to obtain the screening, higher parity, lack of knowledge, and weaker perceptions of benefits.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that offering cheek swab testing rather than blood testing maximises the uptake of testing and is acceptable to the school community. 52 Furthermore, the convenience of offering testing in a school-based setting shows a high uptake rate. 14,15,22 Our study of community attitudes showed that given the opportunity and education, students have increased confidence in their ability to make decisions and feel less affected by peer pressure.…”
Section: Other Concerns and Debatementioning
confidence: 99%
“…Using a two-step consent process requiring both written parental and student consent, participation was lower than for previous one-step school-based programmes, 24 suggesting that consenting processes need to be efficient to facilitate optimal uptake. The strengths of this study are that this is the single largest population-based study to date of genetic screening in schools.…”
Section: Discussionmentioning
confidence: 92%
“…12 Furthermore, there was a more than 95% uptake of screening for Tay Sachs disease and related conditions, in high schools where written parental consent was not required. 24 In addition, when we offered HH screening as part of a workplace study, 90% of university students who were offered screening chose to be screened. 10 The university students were on average 2-3 years older than the students in the current cohort.…”
Section: Discussionmentioning
confidence: 99%